Overcoming a technological discontinuity: The case of the Finnish telecom industry and the GSM - Christopher Palmberg; Olli Martikainen (The Research Institute of the Finnish Economy (ETLA), 2003)
The emergence of the Finnish telecom industry is to a significant extent based on the unprecedented success of Nokia. The case of the GSM is interesting in this context because it is at present the most widely diffused telecom standard in the world, and largely accounts for the international breakthrough of Nokia. Moreover, the GSM was discontinuous to the equipment suppliers compared to previous standards, thereby disrupting the industry. The purpose of this paper is to identify the nature and consequences of these discontinuities to the Finnish industry, and to analyses the conditions and processes that contributed to Nokia's ability to develop the competencies necessary to overcome them. The paper applies the framework of technological systems towards this end and concludes with a discussion on the implications of the findings also to present and future developments of the industry. – GSM ; Finnish telecom ; discontinuity ; design space ; business opportunities – – Suomeen on syntynyt vahva teleala jossa Nokialla on merkittävä asema. GSM-standardi on yleisin telealan standardi, ja se myötävaikutti keskeisesti Nokian menestykseen. Laitevalmistajien kannalta GSM oli osittain epäjatkuva teknologia ja sen syntyminen ja kehittyminen muokkasivat telealan yritysrakenteita. Tämän työpaperin tarkoitus on tarkemmin analysoida GSM:ään liittyviä teknologisia epäjatkuvuuksia ja paneutua näiden epäjatkuvuuksien luomiin haasteisiin ja mahdollisuuksiin Suomen telealan synnyn ja kehityksen sekä Nokian menestymisen näkökulmista. Lähtökohdaksi on otettu kehikko, jossa korostetaan osaamisten, verkostojen ja taloudellisten tekijöiden vuorovaikutusta yritysten ja toimialojen kehityksessä (nk. teknologinen järjestelmä). Tutkimuksen loppuosassa käydään keskustelua myös telealan nykyhetken tilasta ja kehityksestä. – GSM ; Suomen teleala ; teknologia ; epäjatkuvuus ; taloudelliset mahdollisuudet
Keywords: 330; Telekommunikationsgeräteindustrie; Mobilkommunikation; Industriekonjunktur; Finnland